SOSIALISASI PENCEGAHAN DAN PENANGANAN BULLYING DI SMP NEGERI 1 PAKU KECAMATAN PAKU KABUPATEN BARITO TIMUR - Bima, Bima; Nisya, Zahratun; Hasanah, Nisrinaa Nuur; Yuliana, Yuliana (NAWASENA : JOURNAL OF COMMUNITY SERVICE, 2024)
The well-being and development of the younger generation are crucial for a nation's progress. Therefore, parents, educators, and the government have a responsibility to ensure quality education. The Indonesian Constitution guarantees children's rights, including the right to survival, growth, development, and protection from violence and discrimination. However, acts of violence against children, such as bullying, are still prevalent. Technology plays a role in facilitating bullying among students, as it provides a platform for such actions. The lack of awareness and knowledge about bullying in the community and among students further exacerbates the problem. To address this issue, it is important to educate and raise awareness about bullying prevention and handling, specifically targeting students at SMPN 1 Paku in Tampa Village. Socialization programs have been implemented, involving direct lectures on the definition, types, impacts, and regulations related to bullying, as well as discussions and dialogue with participants. The results have shown an improvement in students' understanding of bullying to 97%, knowledge of legal regulations, and awareness of its impact up to 90%.